Religious Freedom of Indigenous Beliefs in Yogyakarta, Indonesia - Bayu Zuhdi, Muhammad; Kalangie, Daniel; Aji Imawan, Satria (SHAHIH: Journal of Islamicate Multidisciplinary, 2022)
Following the recent changes in laws regarding national identity card for the adherents of indigenous beliefs in Indonesia, this study tries to examine 21 types of regulations to see how freedom of indigenous beliefs is in Indonesia from their adherents’ perspective. This is done through conducting semi-structured, in-depth interviews with three groups of indigenous beliefs in Yogyakarta, Indonesia. The types of regulations examined are taken from The Religion and State Project Round 3 by Jonathan Fox of Bar-Ilan University that has been used widely to gather cross-country data on religious freedom. The result of the interviews shows that there are at least four restrictive regulation points, namely on places of worship, surveillance, antireligious campaign and religious education.